A carbon-fiber sheet resistor for MR-, CT-, SPECT-, and PET-compatible temperature maintenance in small animals - Kersemans, V; Gilchrist, S; Wallington, S; Allen, PD; Gomes, AL; Dias, GM; Cornelissen, B; Kinchesh, P; Smart, SC (Grapho Publications, 2019)
A magnetic resonance (MR)-, computed tomography (CT)-, single-photon emission computed tomography (SPECT)-, and positron emission tomography (PET)-compatible carbon-fiber sheet resistor for temperature maintenance in small animals where space limitations prevent the use of circulating fluids was developed. A 250 Ω carbon-fiber sheet resistor was mounted to the underside of an imaging cradle. Alternating current, operating at 99 kHz, and with a power of 1-2 W, was applied to the resistor providing a cradle base temperature of ∼37°C. Temperature control was implemented with a proportional–integral–derivative controller, and temperature maintenance was demonstrated in 4 mice positioned in both MR and PET/SPECT/CT scanners. MR and CT compatibility were also shown, and multimodal MR-CT-PET-SPECT imaging of the mouse abdomen was performed in vivo. Core temperature was maintained at 35.5°C ± 0.2°C. No line-shape, frequency, or image distortions attributable to the current flow through the heater were observed on MR. Upon CT imaging, no heater-related artifacts were observed when carbon-fiber was used. Multimodal imaging was performed and images could be easily coregistered, displayed, analyzed, and presented. Carbon fiber sheet resistors powered with high-frequency alternating current allow homeothermic maintenance that is compatible with multimodal imaging. The heater is small, and it is easy to produce and integrate into multimodal imaging cradles.